Perjumpaan Budaya Lokal dan Islam pada Tradisi Mendirikan Rumah Panggung di Desa Bulutellue - Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
The aim of this study; This study aims to find out the procession of the customs of the Bulutellue Village community towards traditions that link local values and Islamic teachings in building a house on stilts. This study uses the method of observation, interviews, and literature. The results of the study indicate that the tradition of building a house on stilts is a tradition that is carried out from generation to generation as one of the ancestral heritages that is still maintained until now. The values contained in the tradition of building a house are religious values, mutual cooperation values, and solidarity values. Every implementation in the tradition of building a house is believed to have its own meaning, as did mabbarasanji, it is believed to bring blessings to the owner of the house.